PENGARUH KUALITAS PELAYANAN DAN PROMOSI TERHADAP KEPUASAN NASABAH PADA PT KREDIT UTAMA FINTECH INDONESIA DI JAKARTA - Darwin Telaumbanua, Septi; Senen (Journal of Research and Publication Innovation, 2024)
This study aims to determine the influence between service quality and customer satisfaction at PT. Kredit Utama Fintech Indonesia, to find out the influence of promotions on customer satisfaction at PT. Kredit Utama Fintech Indonesia, to find out the influence between service quality and promotion on customer satisfaction at PT. Main Credit of Fintech Indonesia. This research method is Associative with a quantitative approach, the population used is 11,431 respondents and the sample used in this study is 99 respondents obtained from the determination of samples using slovin. Data collection techniques by means of questionnaires, data analysis techniques with validity tests, reliability test, classical assumption tests, multiple regression analysis, hypothesis tests, t tests, f tests, and determination coefficients. The results of the study show that service quality has a partial effect on customer satisfaction, promotion has a partial effect on customer satisfaction and simultaneously service quality and promotion has an effect on customer satisfaction. Based on the results of the coefficient of determination of service quality and promotion on customer satisfaction has an influence contribution of 82% and the remaining 18% is influenced by other factors.